Pengaruh Pemberian Madu Terhadap Kadar Hemoglobin, Berat Badan Lahir Dan Plasenta Pada Ibu Hamil Dengan Anemia - Kartika Asli; Juwita Juwita; Muldaniyah Muldaniyah (Jurnal Keperawatan Muhammadiyah, 2022)
One of the efforts made to prevent anemia in pragnancy  is to use local plants in the community, namely honey. In general honey is effective for producing energy, increasing endurance, and increasing stamina. Honey also contains vitamin C, vitamin A, iron (Fe), and vitamin B12 which functions as the formation of red blood cells and hemoglobin. This study aimed to assess the difference between the intervention group Honey + Fe and the dick Fe group by measuring Hemoglobin levels, birth weight and placenta in pregnant women with anemiaMethods: This research is a quantitative study with a type of quasi experiment research. A sample of 46 people was selected by purposive sampling.Result: The results showed a significant difference in hemoglobin levels between the intervention group Honey + Fe (mean: 11.86 ± 0.94) and the Fe control group (mean: 10.16 ± 1.05) with a value of p = 0,000 (<0,05). The same was found in the measurement of Birth Weight showing a significant difference between the intervention group Honey + Fe (mean 3030 ± 495.53) and the Fe control group (mean 2521 ± 390.75), with a p value: 0,000 (<0.05 ) In contrast to the results of placental weight measurements, no significant differences were found between the intervention group Honey + Fe (mean 520 ± 43.37) and the Fe control group (mean 504 ± 47.65), with a p value: 0.250 (>0.05) .